Upaya Meningkatkan Hasil Belajar Ekonomi Menggunakan Model Pembelajaran Make A Match pada Kelas X IPS 1 SMA Negeri 1 Katingan Hilir - Putu Tiara Kumala Sinta; Bulkani Bulkani (Neraca: Jurnal Pendidikan Ekonomi, 2018)
The researcher aims to find out the activities and find out the improvement in participants' economic learning outcomes. This type of research uses Classroom Action Research (CAR). As for the subjects in this study were students of class X IPS 1 in Katingan Hilir 1 Senior High School totaling 22 students. The instruments used were observation sheets and learning outcomes test questions. The data analysis technique used is qualitative and quantitative. The results of the study show that: (1) The activities of students during the economic learning process are more active. Learning activity cycle I obtained an average score of 2.7 with fairly good criteria, and in the second cycle, the score increased to 3.5 with good criteria. (2) There is an increase in economic learning outcomes after applying the Make a Match learning model. In the first cycle the learning outcomes of students complete with an average of 65 with a data percentage of 64%. Then there is an increase in the second cycle, with an average score of 80 with a percentage of 86%.